Childbirth dynamics in the riverside region of the Brazilian Amazon from the perspective of geospatialization - Liandra Silva Lopes; Laura Maria Vidal Nogueira; Erlon Gabriel Rego de Andrade; Ivaneide Leal Ataíde Rodrigues; Juan Andrade Guedes; Rosinelle Janayna Coêlho Caldas; Paula Gisely Costa Silva (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to analyze the spatial-temporal pattern of childbirths and flow of postpartum women assisted at a regional reference maternity hospital. Methods: ecological study of 4,081 childbirths, between September 2018 and December 2021, at a public maternity hospital in the Baixo Tocantins region, Pará, Brazil. With data collected from five sources, a geographic database was constructed, and spatial analysis was used with Kernel density interpolator. Maps were generated using QGis/3.5 and TerraView/4.3, calculating chi-square (p<0.05). Results: the highest concentrations of normal and cesarean childbirths were observed in Barcarena (n=2,558/62.68%), Abaetetuba (n=750/18.38%), Moju (n=363/8.89%) and Igarapé-Miri (n=219/5.37%). Among the municipalities in the region, ten had obstetric beds, totaling 210 beds. In this scenario, postpartum women traveled up to 288 km to reach the maternity hospital. Conclusions: long distances between certain municipalities of residence and maternity hospital, and low supply of obstetric beds, were identified as risk factors for unfavorable obstetric outcomes.